Web Services, Formal Methods, and Behavioral Types 11th International Workshop, WS-FM 2014, Eindhoven, The Netherlands, September 11-12, 2014, and 12th International Workshop, WS-FM/BEAT 2015, Madrid, Spain, September 4-5, 2015, Revised Selected Papers - Hildebrandt, Thomas; Ravara, António; van der Werf, Jan Martijn; Weidlich, Matthias (Programming and Software Engineering, 2016)
This volume contains the refereed joint proceedings of two initiatives that have been devoted to the formal foundations of complex systems: the workshops WS-FM:FASOCC 2014 and WS-FM/BEAT 2015. The 11th International Workshop on Web Services and Formal Methods: Formal Aspects of Services-Oriented and Cloud Computing, WS-FM 2014, took place in Eindhoven, The Netherlands, in September 2014. The 12th International Workshop on Web Services, Formal Methods, and Behavioral Types, WS-FM 2015, took place in Madrid, Spain, in September 2015. The total of 8 papers presented in this volume was carefully reviewed and selected from 18 submissions. They were organized in topical sections named: expressiveness of behavioral models; service-oriented systems, and behavioral types. .